2014
DOI: 10.1016/j.archoralbio.2013.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Memory-related gene expression profile of the male rat hippocampus induced by teeth extraction and occlusal support recovery

Abstract: Objectives: The present study aimed to identify the effect of memory-related genes on male rats tested for spatial memory with either molar teeth extraction or its restoration by occlusal support using experimental dentures.Design: Memory-related genes were detected from hippocampi of Male Wistar rats (exposed to teeth extraction with or without dentures, or no extraction [control]) (7-week old) after behavioral testing (via the radial maze task) using DNA microarray. The time course of the expression of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 40 publications
(41 reference statements)
1
14
0
Order By: Relevance
“…The expression of S100a9 may be affected by occlusal support. These findings demonstrate that Trh, Tnxa, Nnat and S100a9 genes may affect memory in rats [14].…”
Section: The Possible Molecular Pathogenesis Of the Hippocampal Altersupporting
confidence: 54%
See 2 more Smart Citations
“…The expression of S100a9 may be affected by occlusal support. These findings demonstrate that Trh, Tnxa, Nnat and S100a9 genes may affect memory in rats [14].…”
Section: The Possible Molecular Pathogenesis Of the Hippocampal Altersupporting
confidence: 54%
“…Chronic stress significantly decreased long-term potentiation (LTP) in rat hippocampal CA1 neurons [15,17,22,54]. It is suggested that thytotropin-releasing hormone (Trh), tenascin XA (Tnxa), neuronatin (Nnat), and S100a9 genes may affect memory in rats [14]. Trh is a neuropeptide originally discovered for its function as a hypothalamic factor controlling the synthesis and release of thyrotropin from the pituitary.…”
Section: The Possible Molecular Pathogenesis Of the Hippocampal Altermentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies showed that impairment of masticatory function downregulated memory-related signaling pathways and genes in the hippocampal neurons, including brain-derived neurotrophic factor (BDNF) and its receptor, tropomyosin-related kinase B (trkB) 54, 55. BDNF is a family of nerve growth factors which bind to trkB.…”
Section: Hippocampal Functional Morphological Changes Caused the Mastmentioning
confidence: 99%
“…Memory-related genes that are affected by tooth loss and the recovery of occlusal support were detected [9] in the results of DNA microarray analysis of gene expression in the hippocampus during behavioral memory. As this study was comprehensive, specific expression sites of these genes could not be clarified.…”
mentioning
confidence: 99%